Constraining the population size estimates of the pre-Columbian Casarabe Culture of Amazonian Bolivia - Joseph Hirst; Joy S. Singarayer; Umberto Lombardo; Francis Mayle (PLoS ONE, 2025)
The capacity of Amazonian environments to support large indigenous societies prior to European Contact has long been a contentious area of debate, particularly in regions where pre-Columbian cultures are known to have constructed large, spatially complex earthworks. Here, we provide the first range of supported population estimates for the Casarabe Culture of the Bolivian Llanos de Moxos – one of the most complex pre-Columbian societies yet documented in Amazonia. Between 400 and 1400 CE, the Casarabe Culture inhabited this forest-savanna mosaic landscape, where they constructed hundreds of monumental habitation mounds, integrated by a dense network of causeways and canals, suggesting the former presence of a large, sedentary society. To estimate the population size of this culture, we employed a multifaceted modelling approach – including architectural energetics, maximum carrying capacity, and agent-based modelling – which considers: (i) the number of people needed to build these earthworks; (ii) how many people the local environment could support; and (iii) how their population grew and spread over time. Our results indicate that the Casarabe Culture likely grew to a maximum population of between 10,000 and 100,000 people within a 5020 km2 quadrant of their former territory, representing a density of between 2 and 20 people km-2. These values are considerably larger than both the modern rural population density and the indigenous carrying capacity estimates made for Amazonia more widely, and they support previous interpretations that this culture practiced a form of low-density urbanism.